Concepts of Information/Internet Agents - Markovac, Vesna; Bakić-Tomić, Ljubica; Mateljan, Vladimir (2007)
The complexity of todays "information highway" (Internet) environment demands a new style of human-computer interaction, where the computer becomes an intelligent, active and personalized collaborator (Maes, P.). Agent technology is one of the most vibrant and fastest growing areas of ICT. Information agents perform the role of managing, manipulating or collating information from many distributed sources, they help manage the vast amount of information in wide area networks like the internet. We refer to these class of agents in this paper as information or internet agents (Nwana, H.S.). The information agents would have capabilities of knowing where to look, how to find the information and how to collate it. It is also used term softbot (software robot) which is a fully implemented agent which allows a user to make a high-level request, and the softbot is able to use search and inference knowledge to determine how to satisfy the request in the internet. The biggest challenge is to create a simple user interface so that information search and retrieval using information agents will become as natural for people as picking up a phone or reading a newspaper. Information agents have varying characteristics. There is no standard mode to their operation. Most used internet/information agents are Jasper, Webwatcher and BONOM.
Projekt MZOS
Projekt MZOS
Projekt MZOS
ENG